Cerebral Anatomy of the Spider Monkey Ateles Geoffroyi Studied Using Magnetic Resonance Imaging. First Report: a Comparative Study with the Human Brain Homo Sapiens (2010)
The objective of the present qualitative study was to analyze the morphological aspects of the inner cerebral anatomy of two species of primates, using magnetic resonance images (MRI): spider monkey (A. geoffroyi) and human (H. sapiens), on the basis of a comparative study of the cerebral structures of the two species, focusing upon the brain of the spider monkey and, primarily, its limbic system. In spite of being an endemic Western hemisphere species, a fact which is by its own right interesting for research due to this animal’s social organization and motor functions, the spider monkey (A. geoffroyi) has hardly been studied in regard to its neuroanatomy. MRI was carried out, in one spider monkey, employing a General Electric Signa 1.5 T scanner. This investigation was carried in accordance to international regulations for the protection of animals in captivity, taking into account all protective means utilized in experimental handling, and not leaving behind any residual effects, either physiological or behavioral. From a qualitative point of view, the brains of the spider monkey and the human were found to have similar structures. In reference to shape, the most similar structures were found in the limbic system; proportionally, however, cervical curvature, amygdala, hippocampus, anterior commissure and the colliculi, were larger in the spider monkey than in the human.